2018
DOI: 10.1037/xlm0000425
|View full text |Cite
|
Sign up to set email alerts
|

Aging and confidence judgments in item recognition.

Abstract: We examined the effects of aging on performance in an item-recognition experiment with confidence judgments. A model for confidence judgments and response time (RTs; Ratcliff & Starns, 2013) was used to fit a large amount of data from a new sample of older adults and a previously reported sample of younger adults. This model of confidence judgments allows us to distinguish between changes evidence from memory and changes in decision-related components and it accounts for both RT distributions and response prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 114 publications
(239 reference statements)
0
7
0
Order By: Relevance
“…However, there has to be variability from trial to trial in the stimulus representation (Ratcliff, 1978). To have such variability and a population code, a population code distribution could be assumed with a mean that varied from trial to trial so the combined SD was the across-trial SD in drift rate (as in the RTCON2 model for confidence and multichoice decision making; Ratcliff & Starns, 2009, their Figure 2; Ratcliff & Starns, 2013; Voskuilen & Ratcliff, 2016; Voskuilen, Ratcliff, & McKoon, 2018).…”
Section: Population Code Models and The Two-choice Diffusion Modelmentioning
confidence: 99%
“…However, there has to be variability from trial to trial in the stimulus representation (Ratcliff, 1978). To have such variability and a population code, a population code distribution could be assumed with a mean that varied from trial to trial so the combined SD was the across-trial SD in drift rate (as in the RTCON2 model for confidence and multichoice decision making; Ratcliff & Starns, 2009, their Figure 2; Ratcliff & Starns, 2013; Voskuilen & Ratcliff, 2016; Voskuilen, Ratcliff, & McKoon, 2018).…”
Section: Population Code Models and The Two-choice Diffusion Modelmentioning
confidence: 99%
“…The answers to these questions hint at different interpretations of what underlies the correlation between age differences in response times and age differences in cognitive abilities. There is a growing number of studies on age differences in diffusion model parameters (Ball and Aschenbrenner 2018;Janczyk et al 2018;Madden et al 2010;McGovern et al 2018;Ratcliff 2012, 2013;Ratcliff 2008;Ratcliff et al 2001Ratcliff et al , 2004Ratcliff et al , 2006Ratcliff et al , 2010Spaniol et al 2006Spaniol et al , 2011Thapar et al 2003;Voskuilen et al 2018). Dully et al (2018) gave an overview of the state of the literature in their systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing number of studies on age differences in diffusion model parameters ( Ball and Aschenbrenner 2018 ; Janczyk et al 2018 ; Madden et al 2010 ; McGovern et al 2018 ; McKoon and Ratcliff 2012 , 2013 ; Ratcliff 2008 ; Ratcliff et al 2001 , 2004 , 2006 , 2010 ; Spaniol et al 2006 , 2011 ; Thapar et al 2003 ; Voskuilen et al 2018 ). Dully et al ( 2018 ) gave an overview of the state of the literature in their systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…They tend to be overconfident about the quality of their memory performance. On the other hand, there are almost as many studies that have found only minor or even no age effects on the accuracy of metamemory 28 , 37 39 . Metacognition in other functional domains, e.g., problem solving, linguistics, perception, even seems to elude any age effects 28 , 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%